(untitled) (Natural Resources and Technology, 2023)
The main goal of architecture, as a field that is aimed at designing, planning and organizing the three-dimensional space for human needs, is to make accessible environment. That is one of the main factors for the quality of living in a society. Designing without architectural barriers and raising awareness of the needs of people with disability in relation to architectural design is a current topic today. By including the needs of the people with disabilities, architects show the ethical note of architecture and its connection with responsible behavior towards the environment and the people for whom it was created. When we talk about designing environment for human needs and in range to the human abilities, it doesn`t mean only for physically healthy people. Considering that around 15% of the world`s population has some form of disability, it is very important to design an accessible built environment for as many people as possible. This architectural approach will contribute to increasing the involvement of people with disabilities in daily life activities. The education, as a most important thing in the society, is connected with architectural accessibility to allow free access for children and youth with disabilities, to and in the facilities for education. That allows children and youth with disabilities to develop their intellectual potentials and include them to educational process. It means that accessibility is in a relation to inclusive education and that is important for every society.